Decision Support System In Sous Chef De Partie Selection Using Simple Method Additive Weighting (SAW) (Case Study: Restaurant Goela Batoe) - Iwan Setia Budi; Muhammad Syahrizal (STMIK Budi Darma, 2019)
The SAW method is also known as the weighted addition method. The basic concept of the SAW method is to find the weighted sum of the performance ratings on each alternative of all attributes. The SAW method requires the decision matrix normalization process (X) to a scale that can compare with all available alternative ratings.